Pengaruh Religiusitas Jamaah Masjid Az-Zuhud Petanahan Kebumen Terhadap Perilaku Toleransi Beragama dengan Kepribadian yang Dimilikinya - Saliyo Saliyo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
The research aimed to know influence of one's religiosity to its tolerance behavior. The second  know the personality variables as a moderator variable between variable tolerance behavior  towards one's religiosity. This research is quantitative. The number of research subjects 75 respondents jamaah yasinan Az-Zuhud Mosque Village Petanahan Petanahan District Kebumen. The analysis used by using computerized regression analysis services. Sampling data using probability sampling with random sampling. Data collection using scale. The results showed that no significant relationship between religiosity and religious tolerance a person against person. There is a significant relationship when the personality becomes a moderator variable between religiosity toward tolerance. This means that the religiosity interact with personality as moderator variables, the higher the effect the higher the religiosity of someone's personality influence the behavior  of tolerance